GALERI SEPEDA DI PELAIHARI - Septya Ayu Tri Astuti; Anna Octaviana (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
Pelaihari’s high interest in bicycles is not comparable to the number of bicycle providers. This is evidenced by an increase in bicycle sales up to two times, while the number of providers of bicycles is limited and bicycle sold are not accompanied by explanatory information. There is also no designated place for cycling in Pelaihari. Responding to these problems, the need for a place that serve as a sales center and bicycle information along with supporting facilities in the form of a gallery. The design of the Bicycle Gallery in Pelaihari applies a commercial approach according to Wungow to solve the problem. The commercial approach is applied to the design through 9 aspects of commercial building design.